Transcriptional Analysis of serk1 and serk3 Coreceptor Mutants. Issue 4 (1st November 2016) - van Esse, G. Wilma; ten Hove, Colette A.; Guzzonato, Francesco; van Esse, H. Peter; Boekschoten, Mark; Ridder, Lars; Vervoort, Jacques; de Vries, Sacco C.
Abstract : Transcriptional analysis of serk mutants reveals a novel role of the brassinosteroid coreceptors SERK1 and SERK3 in glucosinolate biosynthesis. Abstract: Somatic embryogenesis receptor kinases (SERKs) are ligand-binding coreceptors that are able to combine with different ligand-perceiving receptors such as BRASSINOSTEROID INSENSITIVE1 (BRI1) and FLAGELLIN-SENSITIVE2. Phenotypical analysis of serk single mutants is not straightforward because multiple pathways can be affected, while redundancy is observed for a single phenotype. For example, serk1serk3 double mutant roots are insensitive toward brassinosteroids but have a phenotype different from bri1 mutant roots. To decipher these effects, 4-d-old Arabidopsis ( Arabidopsis thaliana ) roots were studied using microarray analysis. A total of 698 genes, involved in multiple biological processes, were found to be differentially regulated in serk1-3serk3-2 double mutants. About half of these are related to brassinosteroid signaling. The remainder appear to be unlinked to brassinosteroids and related to primary and secondary metabolism. In addition, methionine-derived glucosinolate biosynthesis genes are up-regulated, which was verified by metabolite profiling. The results also show that the gene expression pattern in serk3-2 mutant roots is similar to that of the serk1-3serk3-2 double mutant roots. This confirms the existence of partial redundancy between SERK3 and SERK1 as well as the promoting or repressive activity of a single coreceptor in multiple simultaneously active pathways.